2012
DOI: 10.5812/hepatmon.852
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Transmitted Hepatitis: Where Do We Stand Now? A One Center Study in Upper Egypt

Abstract: BackgroundDespite progress made in the prevention of transfusion-transmitted infections (TTI) over the last few years, they continue to be a problem in many parts of the world, particularly in multitransfused patients.ObjectivesThe aim of this study was to estimate the prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), and to evaluate the screening and vaccination program among our cohort of multitransfused children from Qena, Upper Egypt.Patients and MethodsOne-hundred children suffering from dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
1
7
1
1
Order By: Relevance
“…Likewise, anti-HCV seropositivity in our patients (11.32%) was lower than those reported among multitransfused patients in Jordan (40%), 2 Egypt (45% to 76%), 4 , 15 Iran (44.7%), 16 India (16% to 26%) 5 and Pakistan (51.3%), 17 which is reflected by the relatively lower prevalence (0.95%) of HCV seropositivity among Syrian blood donors. 8…”
Section: Discussioncontrasting
confidence: 70%
“…Likewise, anti-HCV seropositivity in our patients (11.32%) was lower than those reported among multitransfused patients in Jordan (40%), 2 Egypt (45% to 76%), 4 , 15 Iran (44.7%), 16 India (16% to 26%) 5 and Pakistan (51.3%), 17 which is reflected by the relatively lower prevalence (0.95%) of HCV seropositivity among Syrian blood donors. 8…”
Section: Discussioncontrasting
confidence: 70%
“…The prevalence of HBV infection, here defined as positive HBsAg, among hemophiliacs is lower than that of HCV infection, with different studies finding the prevalence to be 7% - 12% (2, 10, 29-31). However, the rate of positive anti-HBc is much higher (2) (74.6% in our study group).…”
Section: Discussionmentioning
confidence: 98%
“…Absence of positive HBSAg among studied thalassemic patients was also reported by Amli et al, (2008) [ 3 ] and Omar et al, (2011) [ 8 ]. Hepatitis B virus infection occurred in only one patient (2%) out of 50 thalassemics in the study of El Gawhary et al, (2009) [ 32 ], While in the study of El-Faramawy et al, (2012) [ 9 ] 12% of patients were infected with HBV. The decrease in the prevalence of hepatitis B infection in this study and some other studies reflects the efficacy of the vaccination program and effective screening of blood and blood products for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of post-transfusion hepatitis C virus (HCV) infection dropped significantly after the national screening of blood in 1993, more than 20% of children who were multitransfused after that date were HCV-RNA positive [ 7 ]. In Egypt, prevalence rate of HCV antibodies seropositivity in thalassemic children at 2011was 51.7% [ 8 ] while in the study of El-Faramawy et al, (2012) [ 9 ], a prevalence of 48 % was reported.…”
Section: Introductionmentioning
confidence: 99%